Embracing E-Learning for Enhanced Learning Experiences in the Faculty of Economics and Business, Universitas Palangka Raya - Suherman Suherman; Meylinda Sukmani (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
Community service, one of the main tasks according to Tridharma, was carried out to optimize e-learning in the learning process for lecturers and students of the Faculty of Economics and Business (FEB), University of Palangka Raya (UPR). The issue being discussed was e-learning not being optimally used in FEB due to lecturers’ and students’ perceptions that e-learning was not a user-friendly platform. Hence to solve this problem, several implementation methods were being used, which were online and offline coaching clinics on the use of e-learning for lecturers, e-learning workshops for students, preparation of effective guidance modules, and creation of e-learning Standard Operating Procedures (SOP). The result after implementing the community service activities showed that the perceptions about e-learning were resolved after attending the community service activities which resulted in the growth of users from the lecturers and students.